English for Biomedical Engineering: Higher School of Technical Education Students as a Case Study - El Ajraoui, Toufik (European Scientific Journal, ESJ, 2019)
The teaching of English for Biomedical Engineering (EBE) is regarded as one of the most pertinent developments in English language pedagogy. This paper is an attempt to shed light on the experience of teaching EBE to engineering students enrolled at ENSET (Higher School of Technical Education) in Rabat, Morocco. Since the launching of biomedical engineering stream at ENSET, EBE has been concerned with satisfying the students’ expectations and needs by means of a skills-based textbook. In this syllabus the skills range from coping with input texts, such as listening to lectures or tutorials, to producing output texts, such as speaking in realistic situations. Therefore, this investigation aims to measure the adaptability and success of the textbook’s key academic skills through a questionnaire that was devised for ENSET students of biomedical engineering. Based on a statistical data analysis, the results revealed that with such a need based language syllabus the target population could benefit from an awareness of the skills and strategies that helped them get the most out of listening and reading materials and produce spoken and written work of high standard. Yet, the respondents noticed that the textbook is challenging and lexically driven as it heavily relies on terminology used in biomedical fields.